Impact of The Global Stocks Index on The Shariah And Conventional Stocks Index in Indonesia - Dito Prakoso (Islamic Economics Methodology, 2022)
The Islamic capital market plays an important role in the growth of the economy in Indonesia. During its development, the performance of the stock index in a country is often influenced by other stock indices in other countries. This study tries to analyze the dependence of the international stock index towards JII and JCI price, using Autoregression Distributed Lag (ARDL). Results show that there is a long-term cointegration of the global stock index to the Jakarta Islamic Index (JII). On the other hand, there is no cointegration between the global stock index and the Indonesian Composite Stock Price Index (JCI).